Radiological management of postoperative lymphorrhea - Sommer, Christof-Matthias; Pieper, Claus Christian; Offensperger, Florian; Pan, Feng; Killguss, Hansjörg Thomas; Köninger, Jörg; Loos, Martin; Hackert, Thilo; Wortmann, Markus; Do, Thuy; Maleux, Geert; Richter, Götz Martin; et al. (Langenbeck's archives of surgery, 2021)
Postoperative lymphorrhea can occur after different surgical procedures and may prolong the hospital stay due to the need for specific treatment. In this work, the therapeutic significance of the radiological management of postoperative lymphorrhea was assessed and illustrated.
Gesehen am 28.11.2022